Production of commodities by means of commodities: prelude to a critique of economic theory - Sraffa, Piero (Bombay: Vora & Co. Publishers, 1963)
Anyone accustomed to think in terms of the equilibrium of demand and supply may be inclined, on reading those pages, to suppose that the argument rests on a tactic assumption of constant returns in all industries. If such a supposition is found helpful, there is no harm in the reader's adopting it as a temporary working hypothesis. In fact, however, no such assumption is made. No changes in output and (at any rate in Parts I and Parts II) no changes in the proportions in which different means of production are used by an industry are considered, so that no question arises as to the variation or constancy of returns. The investigation is concerned exclusively with such properties of an economic system as do not depend on changes in the scale of production or in the proportions of 'factors'.
Production for Subsistence -- Production with a Surplus -- Proportions of Labour to Means of Production -- the Standard Commodity -- Uniqueness of the Standard system -- Reduction to Dated quantities of Labour -- Joint Production -- The standard system with Joint Products -- Other Effects of joint Production -- Fixed Capital -- Land -- Switch in Methods of Production
Includes index
Keywords: Economics; Production; Production of commodities